Competition, debt maturity, and adjustment speed in China: A dynamic fractional estimation approach - Sultan Sikandar Mirza; Tanveer Ahsan; Raheel Safdar; Ajid Ur Rehman (Journal of Risk and Financial Management, 2020)
The purpose of this study was to investigate the capital structure adjustment rate in different levels of product market competitions. We classified Chinese non-financial listed firms into highly, moderately, and less competitive firms and applied an unbiased dynamic panel fractional estimator on unbalanced panel data of 10,941 firm-year observations during the period of 1998 to 2015. We find that the adjustment rate of highly and less competitive firms towards long-term target capital structure is higher (28.2-29.1%) as compared to the adjustment rate towards short-term target capital structure (18.8-18.9%). On the other hand, the adjustment rate of moderately competitive firms towards long-term target capital structure is slower (22.3%) as compared to the adjustment rate towards short-term target capital structure (25.3%). Further, the adjustment rate of highly and less competitive firms differs significantly between long-term and short-term target capital structure, while the adjustment rate of moderately competitive firms remains steady. Highly competitive large firms follow the limited liability model to adjust their target capital structure and support trade-off theory, while both small and large firms follow the limited liability and predation models in moderately and less competitive environments, respectively.
Keywords: C23; G30; G32; 330; adjustment rate; product market competition; dynamic panel fractional estimator; China